2019
DOI: 10.1111/iep.12322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta‐hydroxy‐beta‐methylbutyrate supplementation on skeletal muscle in healthy and cirrhotic rats

Abstract: Summary Beta‐hydroxy‐beta‐methylbutyrate (HMB) is a leucine metabolite with protein anabolic effects. We examined the effects of an HMB‐enriched diet in healthy rats and rats with liver cirrhosis induced by multiple doses of carbon tetrachloride (CCl4). HMB increased branched‐chain amino acids (BCAAs; valine, leucine and isoleucine) in blood and BCAA and ATP in muscles of healthy animals. The effect on muscle mass and protein content was insignificant. In CCl4‐treated animals alterations characteristic of live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that 12-week HMB supplementation improved muscle performance in compensated cirrhotic patients [25] and increased plasma BCAA in cirrhotic and partially hepatectomized rats [26,27]. However, the effect of oral nutritional supplements (ONS) with HMB on the amino acid profile of patients with decompensated cirrhosis has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that 12-week HMB supplementation improved muscle performance in compensated cirrhotic patients [25] and increased plasma BCAA in cirrhotic and partially hepatectomized rats [26,27]. However, the effect of oral nutritional supplements (ONS) with HMB on the amino acid profile of patients with decompensated cirrhosis has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle is highly responsive to external stimuli such as nutrition and physical activity interventions [7]. In health, a number of nutritional strategies have been shown effective in stimulating muscle protein synthesis, including essential amino acids or their metabolites (such as leucine and HMB) [18] and higher protein doses [19]. Physical activity and dietary intake are modifiable factors associated with the risk of chronic morbidity and mortality in the general population and can positively impact on muscle mass [20,21].…”
Section: Strategies To Attenuate Muscle Loss or Improve Strength Or F...mentioning
confidence: 99%